2018
DOI: 10.3389/fonc.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Axilla in the Era of Breast Cancer Heterogeneity

Abstract: Systemic cancer therapies take into account breast cancer (BC) heterogeneity by targeting pathways specifically involved in some BC subtypes. On the other hand, BC intrinsic radiosensitivity is poorly understood and studied. Hence, radiotherapy personalization in BC is still “work in progress”. In this review, we will summarize the existing data on the management of axillary lymph nodes in BC, the impact of BC radiotherapy on axillary management, the indications for axillary radiotherapy, and biomarkers to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Non-invasive prediction of lymph node status for patients with early-stage invasive breast cancer based on a morphological feature from ultrasound images for local disease control. In the past few years, sentinel node biopsy (SNB) has developed as an alternative to ALND and has become the regular treatment for axillary evaluation in clinically negative patients (4)(5)(6). The SNB is a minimally invasive method and has a significantly lower incidence rate of complications such as lymphedema, numbness, pain, and shoulder impairment than ALND (7,8).…”
Section: Original Articlementioning
confidence: 99%
“…Non-invasive prediction of lymph node status for patients with early-stage invasive breast cancer based on a morphological feature from ultrasound images for local disease control. In the past few years, sentinel node biopsy (SNB) has developed as an alternative to ALND and has become the regular treatment for axillary evaluation in clinically negative patients (4)(5)(6). The SNB is a minimally invasive method and has a significantly lower incidence rate of complications such as lymphedema, numbness, pain, and shoulder impairment than ALND (7,8).…”
Section: Original Articlementioning
confidence: 99%
“…On the one hand, there is a trend towards de-escalation of surgical and systemic therapy (de Meric de Bellefon et al 2018, Mariotto et al 2020Tolaney et al 2015;van der Voort et al 2021;Veronesi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary lymph node dissection could mostly be replaced by sentinel node biopsy and breastconserving surgery could prove a comparable outcome to radical mastectomy. Consequently, therapeutic side effects were reduced drastically [13,25]. In terms of systemic therapy multigene assays helped individualize the therapeutic approach and to reduce the application of adjuvant chemotherapies [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, different management strategies have emerged in axillary lymph node surgery favoring less invasive procedures. To that effect ALND has been replaced by sentinel lymph node biopsy (SNB) in early stages of BC [13]. Especially after the publication of the ACOSOG Z0011 and AMAROSclinical trials which have shown that even in patients with nodal involvement (1 or 2 positive sentinel nodes) -who meet certain criteria -there seems to be no additional bene t of the ALND regarding clinical outcome [14,15].…”
Section: Introductionmentioning
confidence: 99%